Growth in individuals with attenuated mucopolysaccharidosis type I during untreated and treated periods: Data from the MPS I registry. Issue 10 (23rd July 2022) - Polgreen, Lynda E.; Bay, Luisa; Clarke, Lorne A.; Guffon, Nathalie; Jones, Simon A.; Muenzer, Joseph; Flores, Ana Lorena; Wilson, Kathryn; Viskochil, David
Abstract: Mucopolysaccharidosis Type I (MPS I) is caused by deficiency of α‐L‐iduronidase. Short stature and growth deceleration are common in individuals with the attenuated MPS I phenotype. Study objectives were to assess growth in individuals with attenuated MPS I enrolled in The MPS I Registry while untreated and after initiation of enzyme replacement therapy (ERT) with laronidase (recombinant human iduronidase). Individuals in the MPS I Registry with at least one observation for height and assigned attenuated MPS I phenotype as of September 2020 were included. The cohort included 142 males and 153 females 2–18 years of age. Age and sex adjusted standardized height‐for‐age z ‐scores during the natural history and ERT‐treatment periods were assessed using linear mixed model repeated measures analyses. Growth curves were estimated during both periods and compared to standard growth charts from the Center for Disease Control (CDC). There was a significantly slower decline in height z ‐scores with age during the ERT‐treated period compared to the natural history period. Estimated average height z ‐scores in the ERT‐treatment versus the natural history period at age 10 were −2.4 versus −3.3 in females and −1.4 versus −2.9 in males (females first treated 3 year; males <4.1 year). While median height remained below CDC standards during both the natural history and ERT‐treated periods for individuals with attenuated MPS I, laronidase ERT was associated with slower declines in height z ‐scores.